The Interpellation of Misogyny By Female Characters In novel EILEEN By Otessa Moshfegh (2015) - Larassati Alya Septia Ningsih; Delvi Wahyuni (Universitas Negeri Padang, 2020)
This thesis is an analysis of Otessa Moshfegh's novel entitled EILEEN (2015). This analysis is related to the concept of Interpellation by Luis Althusser and Misogyny by SheilaJeffrey and it is under the Feminist literary theory which can reveal issues in the novel. This can be seen in two methods: form of misogynistic women and the way misogyny can get interpellated. The issues raised are women who interpellated the ideology of misogyny and they also did it. Self-judgement, self-objectification, and negative attitude toward other women are the dominant forms of mysoginistic behaviour expressed by female characters in this novel. Family and workplace are the place or the background how this ideology can be interpellated. The analysis shows that misogyny is not only done by men but women also do it. It can be concluded that the ideology formed by these patriarchs is indirectly also supported by women.